m6A-methylase METTL3 promotes retinal angiogenesis through modulation of metabolic reprogramming in RPE cells - Qian Zhou; Xianyang Liu; Huiping Lu; Na Li; Jiayu Meng; Jiaxing Huang; Zhi Zhang; Jiangyi Liu; Wei Fan; Wanqian Li; Xingran Li; Xiaoyan Liu; et al. (Journal of Neuroinflammation)
Abstract Retinal neovascularization (RNV) disease is one of the leading causes of blindness, yet the molecular underpinnings of this condition are not well understood. To delve into the critical aspects of cell-mediated angiogenesis, we analyzed our previously published single-cell data. Our analysis revealed that retinal pigment epithelium (RPE) cells serve a crucial promotional function in angiogenesis. RPE cells were regulated by N6-methyladenosine (m6A). Next, we detected several critical m6A methylase in hypoxic ARPE-19 cells and in oxygen-induced retinopathy (OIR) mice, our results revealed a significant decrease in the level of methyltransferase like 3 (METTL3). METTL3 specific inhibitor STM2457 intravitreal injection or METTL3 conditional knockout mice both showed a significantly reduced neovascularization area of retina. Additionally, the angiogenesis-related abilities of human retinal endothelial cells (HRECs) were diminished after co-cultured with ARPE-19 treated with STM2457 or sh-METTL3 in vitro. Furthermore, through the integration of Methylated RNA immunoprecipitation (MeRIP) sequencing and RNA sequencing, we discovered that the metabolic enzyme quinolinate phosphoribosyltransferase (QPRT) was directly modified by METTL3 and recognized by the YTH N6-methyladenosine RNA binding protein C1 (YTHDC1). Moreover, after over-expressing QPRT, the angiogenic abilities of HRECs were improved through the phosphorylated phosphatidylinositol-3-kinase (p-PI3K)/ phosphorylated threonine kinase (p-AKT) pathway. Collectively, our study provided a novel therapeutic target for retinal angiogenesis.